FROM KNOWLEDGE TO COMPETENCE: ICT COMPETENCE OF A TEACHER - KUBRICKY, Jan (Trends in education, 2008)
The contribution is concerned with ICT competency of a teacher. It analyzes possibilities of competence modulation to its components and proposes the content of the components within an improvement process of teachers' professional formation in the ICT area.
Keywords: knowledge; competence; ICT; professional formation